2009
DOI: 10.1002/bit.22416
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the mechanism of virus removal by Q sepharose fast flow chromatography during the purification of CHO‐cell derived biotherapeutics

Abstract: During production of therapeutic monoclonal antibodies (mAbs) in mammalian cell culture, it is important to ensure that viral impurities and potential viral contaminants will be removed during downstream purification. Anion exchange chromatography provides a high degree of virus removal from mAb feedstocks, but the mechanism by which this is achieved has not been characterized. In this work, we have investigated the binding of three viruses to Q sepharose fast flow (QSFF) resin to determine the degree to which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 44 publications
(65 reference statements)
7
62
0
Order By: Relevance
“…Accordingly, SDS-PAGE of peaks 1 and 2 of the AEX chromatography showed that gp64 was absent in peak 1 and abundant in peak 2, and that most VP6 did not bind to the column. AEX resins have been used to bind viruses (X-MuLV, MMV and SV40) and gp64 through electrostatic interactions [20][21][22]24]. The recovery yield of the AEX step was 65.8%, and the overall yield was 48.1% to this step (Table 1).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Accordingly, SDS-PAGE of peaks 1 and 2 of the AEX chromatography showed that gp64 was absent in peak 1 and abundant in peak 2, and that most VP6 did not bind to the column. AEX resins have been used to bind viruses (X-MuLV, MMV and SV40) and gp64 through electrostatic interactions [20][21][22]24]. The recovery yield of the AEX step was 65.8%, and the overall yield was 48.1% to this step (Table 1).…”
Section: Resultsmentioning
confidence: 98%
“…The loss of VP6 in the concentration step was possibly a result of the removal of unassembled VP6 ( Table 1). The next step in the purification scheme was anion exchange (AEX) chromatography, which is a common step used for the effective recovery, removal or inactivation of viruses in biotechnology products [20][21][22][23]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another well‐studied unit operation that is effective at separating viruses from process streams is anion exchange chromatography . Typical model viruses used in early phase clearance studies have more acidic isoelectric points—6.2 for minute virus of mice (MVM) and 5.8 for MuLV . Because IgG monoclonal antibodies often have basic isoelectric points, there is a large net charge difference between model viruses and many antibody products at neutral pH.…”
Section: Scientific and Technology Considerationsmentioning
confidence: 99%
“…This charge difference is such that antibody flows through the column while viruses adsorb onto the AEX column. When this charge difference is maintained, AEX has been shown to provide robust viral clearance of at least four LRVs across isoelectric points from 7.3 to 8.8 …”
Section: Scientific and Technology Considerationsmentioning
confidence: 99%
“…While viral clearance is highest in the neutral to alkaline pH regime at low conductivity (Strauss et al,2009(Strauss et al, , 2010, a wider design space was initially explored due to the relatively low pI of the molecule. While viral clearance is highest in the neutral to alkaline pH regime at low conductivity (Strauss et al,2009(Strauss et al, , 2010, a wider design space was initially explored due to the relatively low pI of the molecule.…”
Section: Optimization Of the Polishing Stepmentioning
confidence: 99%